Customer attitudes towards internet banking and social media on internet banking in the UK - Wang Y.-Y.; Shanmugam M.; Hajli N.; Bugshan H. (IGI Global, 2023)
Internet banking, a cost saving and productive service delivery channel, has become a new focus of banks along with developments in information and communication technology (ICT). The advancements of ICT may help improve customer satisfaction and influence customer attitudes towards Internet banking, especially on the issue of security. This chapter investigates the attitudes of customers in the UK towards Internet banking by conducting 25 in-depth interviews with various documents to supplement our analysis. Results indicate that security is the most important factor affecting Internet banking adoption in the UK. Furthermore, motivated by the growing importance of social media, this chapter also discusses the role of social media on Internet banking and provides some suggestions on how banks can leverage social media to enhance the adoption rate of Internet banking. The detailed results along with discussions, implications, and limitation are discussed at the end of this chapter. 2015, IGI Global. All rights reserved.